2015
DOI: 10.1124/dmd.115.066340
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Plasma Pharmacokinetics of 3,4-Methylenedioxymethamphetamine and its Phase I and II Metabolites following Controlled Administration to Humans

Abstract: Generally, pharmacokinetic studies on 3,4-methylenedioxymethamphetamine (MDMA) in blood have been performed after conjugate cleavage, without taking into account that phase II metabolites represent distinct chemical entities with their own effects and stereoselective pharmacokinetics. The aim of the present study was to stereoselectively investigate the pharmacokinetics of intact glucuronide and sulfate metabolites of MDMA in blood plasma after a controlled single MDMA dose. Plasma samples from 16 healthy part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Furthermore, recent studies discussed DHMA to play a role in acute cardiovascular effects observed after MDMA consumption [ 54 ]. It was shown that the initial CYP2D6 metabolite DHMA is not present in human plasma in its free form but rather as its sulfate conjugates [ 23 , 55 ], thus making meaningful interpretations of the impact of CYP2D6 difficult because at least one additional metabolic step occurs. Such an analysis after conjugate cleavage will not represent the actual abundance of all metabolites that are present in plasma, thus complicating correlations with potential neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, recent studies discussed DHMA to play a role in acute cardiovascular effects observed after MDMA consumption [ 54 ]. It was shown that the initial CYP2D6 metabolite DHMA is not present in human plasma in its free form but rather as its sulfate conjugates [ 23 , 55 ], thus making meaningful interpretations of the impact of CYP2D6 difficult because at least one additional metabolic step occurs. Such an analysis after conjugate cleavage will not represent the actual abundance of all metabolites that are present in plasma, thus complicating correlations with potential neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…HMMA can be further conjugated by UDP-glucuronyltransferases (UGTs) or SULTs. DHMA 3-sulfate, HMMA sulfate, and HMMA glucuronide were shown to be the main metabolites in plasma [ 23 ] and urine [ 24 ], whereas free DHMA and HMMA were not detectable or only in negligible amounts. A minor pathway includes demethylation to MDA, mainly by CYP2B6, CYP1A2, and CYP3A4 [ 25 , 26 ], followed by demethylenation, O -methylation, and conjugation [ 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…131,137,138 Additionally, the enantiomers of MDMA are metabolized at different rates, with the R-enantiomer having a longer half-life than the S -enantiomer. 139,140, 141 …”
Section: Metabolism and Pharmacokineticsmentioning
confidence: 99%
“…Even though MDMA is ingested in its racemic form, metabolism of rac-MDMA is stereoselective with (+)-(S)-MDMA being preferentially metabolised [5,6] and more potent in inducing euphoria and energy [7,8], whereas the (−)-(R)-MDMA exert higher hallucinogen-like activity than the (+)-(S)-MDMA [9]. This is evident in the stereoselectivity observed in the concentrations of MDMA and related metabolites in urine and plasma samples [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%